Seasonal characteristics of PM1, PM2.5, and PM10 over Varanasi during 2019–2020 - Chauhan, Prashant Kumar; Kumar, Akhilesh; Pratap, Vineet; Singh, Abhay Kumar (Frontiers in Sustainable Cities, 2022)
Particulate Matter (PM) concentrations and Aerosol Optical Depth (AOD) are measured and correlated simultaneously by using a high volume sampler and a MICROTOPS-II Sunphotometer respectively. The present work deals with the characteristics of particulate matter (PM1, PM2.5, and PM10) over Varanasi, from April 2019 to March 2020. Daily variation, as well as seasonal variation, reveals the dominancy of fine mode particles over the Varanasi region in the winter season and the dominancy of coarse mode particles in the summer season, which was further confirmed by calculating the ratio between particulate matter (PM1/PM10 and PM2.5/PM10). This ratio was discovered to be lowest in the summer and highest in the winter. Annual mean concentrations of PM1, PM2.5, and PM10 are found to be 93.91 µgm-3, 111.34 µgm-3, and 180.70 µgm-3 respectively. The seasonal variation shows relatively a higher concentration of PM1, PM2.5, and PM10 in the winter season which may be due to stable meteorological conditions and increased biomass burning in winter. Diurnal and seasonal variations of AOD were also studied during this period. A large and small value of AOD represents the dominancy of fine particles over coarse particles. At 500 nm, maximum (1.17) and minimum (0.44) AOD were measured in December and August of 2019 respectively. There was a statistically significant correlation between PM particles (PM1, PM2.5, PM10) and AOD. Elemental analysis shows that Fluorine and Carbon are the major elements that were observed in selected samples during the post-monsoon and winter season using SEM-EDX analysis.